2011
DOI: 10.1111/j.1095-8312.2010.01577.x
|View full text |Cite
|
Sign up to set email alerts
|

A population on the edge: genetic diversity and population structure of the world's northernmost harbour seals (Phoca vitulina)

Abstract: It is crucial to examine the genetic diversity and structure of small, isolated populations, especially those at the edge of their distribution range, because they are vulnerable to stochastic processes if genetic diversity is low and the isolation level is high, and because such populations provide insight into the consequences of population declines in a broader conservation context. The harbour seal (Phoca vitulina) population in Svalbard is the world's northernmost P. vitulina population. Nothing is known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 105 publications
6
37
1
Order By: Relevance
“…Differentiation between South Australian and Western Australian colonies is not surprising considering the distance (>2200 km) between these two regions. However in comparison to other pinniped studies conducted at similar or larger spatial scales the F ST values reported here between these two regions were higher (Hoelzel et al, 2001;Palo et al, 2001;Coltman et al, 2007;Graves et al, 2009;Andersen et al, 2011;Feijoo et al, 2011). Strong genetic partitioning between South Australian and West Australian colonies is also evident with mtDNA data (significant pairwise ST values ranged from 0.83 to 0.94, Campbell et al, 2008).…”
Section: Genetic Diversity and Differentiationcontrasting
confidence: 57%
“…Differentiation between South Australian and Western Australian colonies is not surprising considering the distance (>2200 km) between these two regions. However in comparison to other pinniped studies conducted at similar or larger spatial scales the F ST values reported here between these two regions were higher (Hoelzel et al, 2001;Palo et al, 2001;Coltman et al, 2007;Graves et al, 2009;Andersen et al, 2011;Feijoo et al, 2011). Strong genetic partitioning between South Australian and West Australian colonies is also evident with mtDNA data (significant pairwise ST values ranged from 0.83 to 0.94, Campbell et al, 2008).…”
Section: Genetic Diversity and Differentiationcontrasting
confidence: 57%
“…There is already evidence that populations of key Arctic species dependent on ice are under stress, as reflected in declining growth, condition, and reproductive output, particularly for the polar bears and some of the seal species most dependent on ice (Renaud et al 2008;Wassmann et al 2011;Andersen et al 2011). As their populations decline with ice loss, they are expected to hybridize with closely related species, a process eventually leading to the loss of these species (Kelly et al 2010).…”
Section: Tipping Points In the Arctic Marine Ecosystemmentioning
confidence: 99%
“…This small, isolated population of ca. 2000 animals (Merkel et al 2013) has low genetic diversity (Andersen et al 2011); it is Red-listed in Norway and hence protected from harvesting. The haul-out behaviour of this population has been studied intensively (Reder et al 2003), and concomittantly with the current stud (see Hamilton et al 2014), but the at-sea behaviour of adult harbor seals re mains largely undocumented.…”
Section: Introductionmentioning
confidence: 99%